Nutritive value of fermented coconut meal in ration of laying ducks with various phosphorous levels - Sinurat, A.P; Purwadaria, T; Habiebie, A; Pasaribu, T; Hamid, H; Rosida, J; Haryati, T; Sutikno, I (Indonesian Journal of Animal and Veterinary Sciences, 1998)
A series of experiment was conducted to improve the utilization of coconut meal in poultry ration . A bioprocess (fermentation) approach was adopted. Coconut meal was fermented followed by an enzymatic process at room temperature or 50 OC.The nutritive value of the fermented products was determined chemically. Product with the highest nutritive value was then used for a feeding trial to study the interaction effect between dietary levels of fermented coconut meal and phosphorous level on the performances of laying ducks. Nine experimental diets were formulated, i.e ., the factorial of 3 levels of fermented coconut meal (0, 30 and 40%) and 3 levels of total phosphorous (0.6, 0.8 and 1 .0%) . The diet was fed to pullet ducks and the performances of the ducks were observed for 16 weeks of production period. The results showed that the nutritive value of coconut meal increased by fermentation and the highest yield was achieved when the enzymatic process was performed at 500C. There was no significant interaction effect between dietary fermented coconut meal levels and the phosphorous levels on all parameters observed, except on egg weight. Inclusion of fermented coconut meal in the ration up to 30% did not produce negative effects on the productivity oflaying ducks, however, higher levels (40%) ofinclusion reduced the egg size Â  Keywords: Coconut meal, fermentation, ducks, egg production